Effect of soy proteins Vs soy isoflavones on lipid profile in postmenopausal women - Jassi, H. K. (Springer-Verlag, 2010)
Soy isoflavones and soy proteins are being considered as possible alternatives to postmenopausal hormone replacement therapy. This study was undertaken to evaluate effects of these two preparations on symptoms and lipid profile in postmenopausal women. The study was done in 75 postmenopausal women with FSH levels = 30 mIU/ml. These women were randomly divided into 3 groups (n=25). Study group I was given soy proteins 30gm/day containing 60 mg soy isoflavones. Study group II was given soy isoflavones (60 mg/day). The control group was given casein protein 30 gm/day. The menopausal symptoms were assessed by Kupperman Index. Fasting blood samples were analyzed for serum lipid profile, apolipoprotein A1 and B, Leutenizing Hormone (LH) and Follicle-Stimulating Hormone (FSH) at the beginning of therapy, 4 and 12 weeks after initiation of therapy. A highly significant improvement in postmenopausal symptoms was observed in both the study groups. A highly significant improvement was seen in serum lipid profile and Apolipoprotein A1 and B in women taking soy proteins whereas women taking soy isoflavones demonstrated significant improvement in serum triglycerides only. Both soy proteins and soy isoflavones are helpful in alleviating postmenopausal symptoms but soy proteins offer a greater health advantage due to their beneficial effect on serum lipid profile.